STRATEGI MENINGKATKAN PEREKONOMIAN MASYARAKAT MELALUI PENGEMBANGAN EKOWISATA MANGROVE DI KABUPATEN SUMBAWA - I Ketut Aria Darmawan; I Ismawati; Subhan Purwadinata (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine the strategy for improving the community's economy through the development of mangrove ecotourism in Labu Sawo Hamlets, Sumbawa District. The type of data used is qualitative which is obtained directly from primary sources using interview techniques. The informants in this study were the Head of Penyaring Village, Head of Pokdarwis, Maritime Service, Tourism Manager and the coastal community of Labu Sawo Hamlets, totaling 10 people. The data used in this study was analyzed using the SWOT analysis technique to formulate various alternative strategies to improve the community's economy through the development of mangrove ecotourism in Labu Sawo Hamlets, Sumbawa District. The data was analyzed using the SWOT analysis technique. The results of this study showed that the SWOT analysis in formulating a strategy to improve the community's economy through the development of mangrove ecotourism in Labu Sawo Hamlets, Sumbawa Regency produces four alternative strategies, namely SO strategy, WO strategy, ST strategy and WT strategy. The resulting alternative strategies are maintaining and developing the sustainability of mangrove vegetation and diverse flora and fauna; increasing cooperation with the government in providing tourism facilities and infrastructure; increase public and tourist awareness in protecting mangrove ecosystems; create uniqueness that is different from other tourist attractions; improving the quality of managing human resources through education and training activities; and optimizing the use of various information media as a promotional tool to introduce ecotourism objects to the public.